UMP gets second placing in NACES 2010 - UMP, PNC
Ten students from Faculty of Chemical & Natural Resource Engineering, Universiti Malaysia Pahang (UMP) were selected to take part in a competition of National Chemical Engineering Symposium at Shah Alam on December 19, 2010.